Pengembangan Perangkat Pembelajaran pada Mata Pelajaran Dasar Listrik dan Elektronika - Cendra Kurniadi; Aslimeri Aslimeri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Learning devices are all the tools and materials used by the teacher to carry out the learning process. Every teacher in an education unit is obliged to compile a complete and systematic learning tool so that learning is interactive, inspirational, fun, challenging, motivates students to actively support, and provides sufficient space for initiative, creativity, independence, according to their talents, interests, and develop physical and psychological students. This research on the development of learning tools in the form of lesson plans for basic electricity and electronics is aimed at producing valid and practical learning tools. This study uses a research development method (Research and Development) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subject of this research is a learning tool in the form of RPP with research respondents by the teacher. From the results of the validity test of learning tools in the form of lesson plans obtained from teacher respondents in the valid category and the practicality test from the teacher obtained in the practical category. The results of this study indicate that the learning tools in the form of lesson plans made for Basic Electricity and Electronics subjects are suitable for use as learning tools.